Donors brain-dead after successful resuscitation of cardiac arrest: Early outcome and postoperative complications of lung recipients. (March 2023) - Atchade, Enora; Arsène, Adrien; Jean-Baptiste, Sylvain; Tran Dinh, Alexy; Tanaka, Sébastien; Stern, Jules; Lortat-Jacob, Brice; Rosencwajg, Sacha; Goletto, Tiphaine; Mal, Hervé; Ben Adballah, Iannis; Castier, Yves; et al.
Abstract: Background: The outcomes of lung transplantation (LT) recipients who received a graft from a brain-dead donor after successful resuscitation from cardiac arrest (CA donors) have been poorly described. This study compared the one-year survival of LT recipients depending on the CA status of the donor. Methods: This prospective observational single-centre study analysed all consecutive patients who underwent LT at Bichat Claude Bernard Hospital, Paris, between January 2016 and December 2020. All donors who experienced CA prior to organ donation, regardless of rhythm or duration, were considered CA donors. The postoperative complications and outcomes of LT recipients were analysed. The one-year survival was compared using Kaplan-Meier curves and log-rank tests. Independent risk factors for one-year mortality were assessed using multivariate analysis (p < 0.05 was considered significant). The Paris North Hospitals Institutional Review Board approved the study. Results: A total of 236 LT recipients were analysed and 66 (28%) received a graft from a CA donor. The median durations of no/low flow were 4 [0–10]/20 [15–30] minutes, respectively. Shockable and non-shockable rhythms were observed in 11 (17%) and 47 (72%) of the CA donors, respectively. The characteristics of the grafts and early postoperative complications were not different in the CA and non-CA groups. Receiving a graft from a CA donor was not an independent risk factor for recipient one-year mortality. Conclusion: Receiving a graft from a CA donor did not worsen the outcome of LT recipients. Acceptation of these grafts must be systematically considered to increase the pool of available grafts.